Effects of temperature on type approval testing of ballast water treatment systems. (25th March 2013) - Drillet, Guillaume; Schmoker, Claire; Trottet, Aurore; Mahjoub, Mohamed‐Sofiane; Duchemin, Matthieu; Andersen, Martin
Abstract: To limit the risk associated with invasion of habitats by exogenous species, the International Convention for the Control and Management of the Ships' Ballast Water and Sediments was adopted in February 2004 and may soon enter into force. The International Maritime Organization (IMO) has produced guidelines to assess the efficacy and reliability of Ballast Water Treatment Systems (BWTS), but no guidance on how to take temperature into account during test cycles has been provided yet. Temperature is one of the main factors influencing the distribution and ecology of organisms along latitudes. Its increase results in higher grazing, growth, and reproduction rates of zooplankton. Under dark conditions, phytoplankton loss is also increased due to faster natural decay as well as enhanced top down control from zooplankton. Increased temperatures also improve the efficacy of chemical treatment, whereas the decay rates of disinfectants and their byproducts are potentially accelerated. The IMO guidelines for the type approval of BWTS should be amended to include recommendations on how to take temperature into account. Failing to ensure comparability and reliability between tests may pose a threat to the environment and may create problems for those attempting to apply BWTS. We propose to use a fixed Q10 value and a temperature of reference to adjust the retention time in ballast water tanks during testing. Integr Environ Assess Manag 2013; 9: 192–195. © 2013 SETAC